Sport for Reconciliation? Federal Sport Policy in Settler-Colonial States - Forde, Shawn; Giles, Audrey R.; Stewart-Withers, Rochelle; Rynne, Steven; Hapeta, Jeremy; Hayhurst, Lyndsay; Henhawk, Daniel (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
In settler-colonial contexts, the use of sport for reconciliation (SFR) has received increasing attention from national governments and their sporting agencies, though researchers have yet to track the development of SFR across settler colonial contexts. In this study, we examined how government sport policies in Australia, Canada, and Aotearoa/New Zealand frame understandings of reconciliation. Through the application of both policy and frame analysis to 82 documents from 1970s to 2020, we argue that policy framings have shifted from presenting Indigenous peoples as a homogenous disadvantaged group to more inclusive considerations of Indigenous cultures. Nevertheless, an assimilative agenda continues to guide policy, as understandings of Indigenous self-determination are absent from sport policy documents and reconciliation is primarily understood as Indigenous peoples being reconciled to the status quo.